A large cemento-ossifying fibroma in the maxilla of 12-year-old boy: A case report - Intan N. Dhewayani; Eky Nasuri; Muhammad A. Latief (Journal of Dentomaxillofacial Science, 2021)
Objective: Cemento-ossifying fibroma is a rare benign lesion of the head and neck region. Only a few children had this lesion. Case Report: A 12-years old man came to the RSCM hospital in the oral and maxillofacial department. He complains of a lump in the left cheek since 4 years ago. The patient was referred to RSCM Hospital with pathological anatomy result was cemento ossifying fibroma. A recent complaint was nasal congestion on the left side, neither fluid nor blood discharge from mouth and nose. Result: Cemento-ossifying fibroma can occur in children 12 years old, and radiological and histopathological appearance Conclusion: A critical approach towards the clinical, radiological, and histopathological features is the main subject for the best result.